Homogenisation model for calculating multi‐point grounding current of transformer core. Issue 2 (24th January 2019) - Zhou, Lijun; Jiang, Junfei; Liu, Huancheng; Gao, Shibin; Li, Wei; Zhang, Chenqingyu
Abstract : Multi‐point grounding of the core is one of the common transformer faults. In this study, a homogenisation model based on the finite element method is developed for calculating multi‐point grounding current of the transformer core. The equivalent conductivity in the direction normal to the laminations is determined by the analysis of fault current distribution and calculation of anisotropic resistances of the iron core, especially, considering the influence of insulation coating on the silicon steel sheet. The validity of the proposed model is verified by comparing the three‐dimensional finite element simulation results with the experimental results. Finally, two typical faults are simulated to further study the characteristics of multi‐point grounding current based on a distribution transformer, which may be useful for the optimisation of transformer core design.